ISOTOPIC-RADIOGEOCHEMICAL ANALYSIS OF GROUNDWATER AT THE KALUSH-GOLINSKY POTASSIUM SALT DEPOSIT - Yа. Malkova; I. Kovalenko; Dolin V.; Panasyuk M.; Demikhov Yu.; Sosonna N.; Bagriy S.; Kuzmenko E. (Геохімія техногенезу, 2022)
The main potential sources of groundwater salinity of the gravel-pebble aquifer of the Kalush-Golinsky potassium salt deposit were analyzed. The distribution of tritium (3H) in groundwater and surface water of the territory adjacent to the Dombrovsky quarry was investigated. By isotope-geochemical methods the directions and levels of possible sources influence of chemical pollution of underground waters were analyzed: waters of Dombrovsky quarry, tailings and sludge collector, salt dumps, saline soils. Concentrations of 3H vary from values of 4-6 Bq/L in underground waters to 9-12 Bq/L in surface natural waters (rivers Sivka and Limnitsa) and surface technogenic waters (tailing pits, sludge collector, Dombrovsky quarry and others). The obtained data using isotope method allow us to determine some hydrogeological and hydrochemical conditions of gravel-pebble aquifer, which is used for drinking water supply of Kalush (Ivano-Frankivsk region). Formation of the underground flow of highly concentrated brines is primarily due to the radial flow from the tailings and sludge reservoir, which allows us to identify them as sources of technogenic pollution. Enrichment with heavy hydrogen isotopes (3H) is observed in water samples from open brine storages formed during exploitation of Kalush-Golinsky potassium salt deposit and after its retirement from exploitation. The growth of isotope concentrations is also characteristic of groundwater samples from wells located downstream of groundwater from surface technogenic water storages (tailings pond, sludge reservoir, etc.). The results of research are planned to use in creating a 3-dimensional mathematical model and predicting changes in the hydrogeological conditions near the Dombrovsky quarry and Dobrovlyansky water intake of drinking groundwater.